Trade Exposure, Export Intensity, and Wage Volatility: Theory and Evidence - Traca, Daniel A. (The Review of Economics and Statistics, 2005)
This paper addresses the link between trade exposure and wage volatility. First, it shows, in a simple model, that trade exposure magnifies the impact of domestic productivity shocks on industry-specific labor demand, particularly for the less export-intensive industries, and that, if labor is not perfectly mobile, this implies a rise in wage volatility. Then, it tests these predictions, using industry data. The empirical results confirm that wage volatility increases with an industry's degree of openness, and that it declines with an increase in the industry's export intensity.